(untitled) (International Journal of Engineering and Computer Science, 2018)
Vehicular Ad-hoc Network (VANET) in the recent years have emerged as a most attractive topic for researchers and automotive industries due to their tremendous potential to improve traffic safety, efficiency and other added services.The routing in VANET is the most challenging part of research.. Research in the field of Vehicular ad-hoc network technology has provided us with a new chapter in the world of wireless communication. In this paper we are propose a cluster based routing approach for VANET and compare its performance with existing routing protocols. This new approach will have an aim to minimize end to end delay and increase the overall network throughput. NS2 is used to conduct simulation.